Pengaruh Ukuran Bank, NPF, dan BOPO terhadap Stabilitas Bank Umum Syariah Periode 2020-2024 - Kartika Eka Rosewanti; Maziyah Mazza Basya; Ade Irma Suryani Lating (ALSYS, 2026)
Although the stability of Islamic banking is highly crucial for economic resilience, studies that specifically examine the effects of bank size, Non-Performing Financing (NPF), and Operating Expenses to Operating Income (BOPO) on the stability of Islamic Commercial Banks (BUS) using the Z-Score proxy remain limited and have shown varied results. This study aims to analyze the effects of bank size, NPF, and BOPO on the stability level of BUS in Indonesia during the 2020–2024 period. This study used an explanatory quantitative approach with a panel data regression design. The research sample consisted of 10 BUS selected through purposive sampling. Data were collected through documentation techniques in the form of quarterly financial reports and analyzed using EViews 14 with the Random Effect Model (REM) approach. The results showed that, partially, bank size had a positive and significant effect on BUS stability. Conversely, NPF and BOPO had negative and significant effects on BUS stability. Simultaneously, the three variables contributed 51.4% to bank stability. These findings contribute to the development of Financial Stability Theory and expand understanding of the determinants of Islamic bank resilience. The conclusion of this study affirms the importance of strengthening assets, managing financing risk, and improving operational efficiency in maintaining BUS stability. The implications of this study include theoretical contributions to the development of Islamic finance literature, as well as practical implications for banking management in reducing operational expenses and financing risk in order to strengthen bank stability.